Automatic fingerprint center point determination by using modified directional field and morphology - Teoh, Andrew Beng Jin; Ong, Teng Sian; Sek, Y. W.; Ngo, David Chek Ling (2003)
Accurate and reliable center point determination of the fingerprint is an essential pre-processing step for the image based fingerprint recognition approach. This step is particularly important since a reference point is required to cancel the variation in position of the reference and testing fingerprint image. This paper illustrated an automatic center point determination algorithm that couples the modified averaged square directional field (MASDF) with morphological operation, in order to pinpoint the center point of the fingerprint efficiently and accurately. The experiment result shows only 3.13% rejection rate for the false center point by using the proposed method.